Pengaruh Content Marketing dan Storytelling Marketing di Media Sosial Instagram terhadap Brand Awareness Perusahaan : Studi Kasus pada Perkebunan Durian Aa Kadu - Tazkia Normatiena Muhyiddin; Aditia Abdurachman; N. Nelis Febriani SM; Alfin Nur Arifah (Universitas Nusantara PGRI Kediri, 2026)
This study aims to determine the effect of content marketing and storytelling marketing on Instagram social media on brand awareness at AA Kadu Plantation. The background of this study departs from the increasing importance of social media as a digital marketing tool, especially in building brand awareness. This study uses a quantitative method with a survey technique by distributing questionnaires to 100 respondents who are consumers of AA Kadu Plantation. The data obtained were then analyzed using multiple linear regression analysis to test the influence between variables. The results show that content marketing has a positive and significant effect on brand awareness, as well as storytelling marketing has a positive and significant effect on brand awareness. The conclusion of this study is that the implementation of consistent, high-quality, and creative content marketing and storytelling marketing strategies through Instagram can increase consumer brand awareness of AA Kadu Plantation.